Depth‐based differentiation in nitrogen uptake between graminoids and shrubs in an Arctic tundra plant community. (30th December 2017) - Wang, Peng; Limpens, Juul; Nauta, Ake; van Huissteden, Corine; Quirina van Rijssel, Sophie; Mommer, Liesje; de Kroon, Hans; Maximov, Trofim C.; Heijmans, Monique M.P.D.
Abstract: Questions: The rapid climate warming in tundra ecosystems can increase nutrient availability in the soil, which may initiate shifts in vegetation composition. The direction in which the vegetation shifts will co‐determine whether Arctic warming is mitigated or accelerated, making the understanding of successional trajectories urgent. One of the key factors influencing the competitive relationships between plant species is their access to nutrients, depending on the depth where they take up most nutrients. However, nutrient uptake at different soil depths by tundra plant species that differ in rooting depth is unclear. Location: Kytalyk Nature Reserve, northeast Siberia, Russia. Methods: We injected 15 N to 5 cm, 15 cm and the thaw front of the soil in a moist tussock tundra. The absorption of 15 N by grasses, sedges, deciduous shrubs and evergreen shrubs from the three depths was compared. Results: The results clearly show a vertical differentiation of N uptake by these plant functional types, corresponding to their rooting strategy. Shallow‐rooting dwarf shrubs were more capable of absorbing nutrients from the upper soil than from deeper soil. Deep‐rooting grasses and sedges were more capable of absorbing nutrients from deeper soil than the dwarf shrubs. The natural 15 N abundances in control plants also indicate that graminoids can absorb more nutrients from the deeper soil than dwarf shrubs. Conclusions: Our results show that graminoids and shrubs in the Arctic differ in their N uptake strategies, with graminoids profiting from nutrients released at the thaw front, while shrubs mainly forage in upper soil layers. Our results suggest that tundra vegetation will become graminoid‐dominated as permafrost thaw progresses and nutrient availability increases in the deep soil. Abstract : We show that in Arctic tundra, shrubs and graminoids have different strategies in nutrient uptake. Shrubs mainly take up nutrients from the surface soil, while graminoids also forage at the thaw front. Our results suggest that tundra vegetation will become graminoid‐dominated as permafrost thaw progresses and nutrient availability increases in the deep soil.